The development of nursing care of the sick in Western Europe in the 18th and the first half of the 19th centuries - Jerzy Supady (University of Applied Sciences in Tarnow, Poland, 2019)
The Enlightenment ideology and the French Revolution had a very negative impact on the activities of religious congregations in respect of nursing care of the sick in hospitals in the 18th century. Emperor Napoleon I attempted to improve the existing situation by restoring the right for nursing care to nuns. In the first half of the 19th century, in Germany catholic religious orders had the obligation to provide nursing care and in the 30's of the 19th century the Evangelical Church also joined charity work in hospitals by employing laywomen, i.e. deaconesses.